EVALUASI STRUKTUR TAHAN GEMPA PADA BANGUNAN GEDUNG GOLD COAST OFFICE JAKARTA UTARA - Laatifah, Maratul (JITSi : Jurnal Ilmiah Teknik Sipil, 2023)
Abstract— Indonesia is a country that is in an active tectonic zone because three large and small plates meet, namely the Indo-Australian plate, the Eurasian plate, and the Pacific plate, so Indonesia is a zone prone to earthquakes. The Gold Coast Office building, with coordinates -6.102458°.106.739800°, is located on Kapuk Island, North Jakarta. It has a building area of 129,862 m2 and a building height of 125.8 m. The research on the evaluation of earthquake-resistant structures aims to determine the structural performance of the Gold Coast Office Building based on the parameters of base shear, mass participant ratio, and displacement. The results of the study were used to determine the performance evaluation of the structure based on service limit performance and ultimate limit performance. The dynamic analysis of the response spectrum method based on SNI 1726-2019 (2019) was used as the method of this research. The displacement value due to the influence of the planned earthquake in the X direction max is 0.0085 m and in the Y direction max is 0.0086 m. It can be stated that the Gold Coast Office North Jakarta building is safe and meets the performance requirements for building structures based on service limit performance with requirements (0.03/R)*H = 0.0176 m. The displacement value due to the influence of the planned earthquake in the X direction max is 0.0418 m and in the Y direction max is 0.0419 m, so it can be stated that the Gold Coast Office North Jakarta building is safe and meets the performance requirements for building structures based on ultimate limit performance with requirements (0.02*H) = 0.082 m.  Keywords — Building Structure, Dynamic Response Spectrum, Earthquake, Office, Reinforced Concrete.   Abstrak— Indonesia merupakan negara yang berada pada zona tektonik yang aktif karena dipertemukan 3 lempeng yang besar dan kecil yakni lempeng Indo-Australia, lempeng Eurasia dan lempeng Pasifik, sehingga Indonesia termasuk zona rawan gempa. Gedung Gold Coast Office dengan titik koordinat -6,102458°.106,739800° berada di Pulau Kapuk Jakarta Utara, memiliki luas bangunan ±129,862 m2  dengan tinggi bangunan mencapai 125,8 m. Penelitian evaluasi struktur tahan gempa bertujuan untuk mengetahui kinerja struktur gedung Gold Coast Office berdasarkan parameter base shear, mass participant ratio, dan displacement. Hasil dari penelitian untuk mengetahui evaluasi kinerja struktur berdasakan kinerja batas layan dan kinerja batas ultimit. Metode yang digunakan adalah analisis dinamik metode respon spektrum berdasarkan SNI 1726-2019, (2019). Nilai displacement akibat pengaruh gempa rencana arah X didapat terbesar 0,0085 m dan arah Y didapat terbesar 0,0086 m sehingga dapat dinyatakan gedung Gold Coast Office Jakarta Utara aman dan memenuhi syarat kinerja struktur gedung berdasarkan kinerja batas layan dengan persyaratan (0,03/R)*H = 0,0176 m. Nilai displacement akibat pengaruh gempa rencana arah X didapat terbesar 0,0418 m dan arah Y didapat terbesar 0.0419 m sehingga dapat dinyatakan gedung Gold Coast Office Jakarta Utara aman dan memenuhi syarat kinerja struktur gedung berdasarkan kinerja batas ultimit dengan persyaratan (0,02*H) = 0,082 m.   Kata kunci — Struktur Bangunan Gedung, Gempa, Perkantoran, Beton Bertulang, Dinamik Respon Spektrum